ANALISIS KEPUTUSAN PEMBELIAN TIKET ONLINE BIOSKOP MELALUI APLIKASI TIX.ID - Aditya Wulandari (2020)
This research is a quantitative study aimed at analyzing factors that influence purchasing decisions, especially the factors of ease of use, trust, and discount. The population in this research is South Jakarta cinema visitors who purchases tickets online through the TIX.ID application. The sample size was taken as much as 75 respondents, with a probability sampling technique using the simple random sampling method. Data collection is done through the spread of google form online questionnaires. The analytical technique used are Structural Equation Modeling (SEM) based variances or called Partial Least Square (SmartPLS software version 3.2). The results of this research are (1) 0.465 ease of use has a positive and significant effect on purchasing decisions, (2) 0.220 trust has a positive and significant effect on purchasing decisions, (3) 0.243 discounts have a positive and significant effect on purchasing decisions. With R-Square Adjusted produces 62.8% Keywords: Ease of Use, Trust, Discounts, and Purchasing Decisions